1998
DOI: 10.1107/s0909049597015811
|View full text |Cite
|
Sign up to set email alerts
|

Development of X-ray photoemission electron microscopy (X-PEEM) at the SRS

Abstract: The use of synchrotron radiation sources for X-ray spectroscopy is a well known and developed ®eld. The majority of applications, however, have been limited to studies of materials containing only a single phase of the element of interest. Owing to limited availability of suitable instrumentation, the study of materials comprising intergrowths of different phases has presented dif®culties in analysis. The majority of natural materials, including mineralogical samples, fall into this category. However, by apply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…1995). The potential for XPEEM to be applied to geomaterials was explored by Smith et al. (1998, 2004), using an in‐house prototype PEEM and by Schofield et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1995). The potential for XPEEM to be applied to geomaterials was explored by Smith et al. (1998, 2004), using an in‐house prototype PEEM and by Schofield et al.…”
mentioning
confidence: 99%
“…Within mineralogy, bulk 2p XAS of powdered samples was developed for fingerprinting and quantifying oxidation states and site symmetries of geomaterials (de Groot et al 1992, van der Laan et al 1992, Cressey et al 1993, Pattrick et al 1993, Schofield et al 1993, 1995a, b, Henderson et al 1995, Li et al 1995. The potential for XPEEM to be applied to geomaterials was explored by Smith et al (1998Smith et al ( , 2004, using an in-house prototype PEEM and by Schofield et al (2002) zone textured regions indicating increased oxidation at the edges of these zones. The spatial resolution of the XPEEM achieved was between 110 and 150 nm, which precluded the study of either the previously reported 10 nm precipitates of tetrataenite within the bulk taenite or any antitaenite.…”
mentioning
confidence: 99%
“…The beamline has a spherical-grating monochromator, yielding very high photon flux (2 × 10 12 photons S −1 at 800 eV in a 0.4 mm × 0.2 mm) with spatial resolution better than 50 nm. [26,27] The emitted photoelectrons were accelerated toward an electron lens column and projected onto an aluminum coated yttrium aluminium garnet crystal screen. The real-time, sample surface im-ages were acquired by a charge coupled device detector mounted behind the screen in total electron yield mode.…”
Section: Methodsmentioning
confidence: 99%
“…Another advantage of PEEM is the ability to easily extract data from any given point on the surface, allowing one to investigate how a surface changes with distance from a feature or grain interface. PEEM has been applied to heterogeneous minerals by Smith et al (1998) and Schmidt et al (2001) to image the distribution of mineral phases across natural samples. However, these studies were concerned with identification of mineral phases within heterogeneous samples, rather than the study of surface processes.…”
Section: Introductionmentioning
confidence: 99%